KCa channel activation normalizes endothelial function in Type 2 Diabetic resistance arteries by improving intracellular Ca(2+) mobilization - Mishra, Ramesh C (Metabolism, 2020)
BACKGROUND: Endothelial dysfunction is an early pathogenic event in the progression of cardiovascular disease in patients with type 2 diabetes (T2D). Endothelial KCa2.3 and KCa3.1 K(+) channels are important regulators of arterial diameter, and we thus hypothesized that SKA-31, a small molecule activator of KCa2.3 and KCa3.1, would positively influence agonist-evoked dilation in myogenically active resistance arteries in T2D. METHODOLOGY: Arterial pressure myography was utilized to investigate endothelium-dependent vasodilation in isolated cremaster skeletal muscle resistance arteries from 22–24 week old T2D Goto-Kakizaki rats, age-matched Wistar controls, and small human intra-thoracic resistance arteries from T2D subjects. Agonist stimulated changes in cytosolic free Ca(2+) in acutely isolated, single endothelial cells from Wistar and T2D Goto-Kakizaki cremaster and cerebral arteries were examined using Fura-2 fluorescence imaging. MAIN FINDINGS: Endothelium-dependent vasodilation in response to acetylcholine (ACh) or bradykinin (BK) was significantly impaired in isolated cremaster arteries from T2D Goto-Kakizaki rats compared with Wistar controls, and similar results were observed in human intra-thoracic arteries. In contrast, inhibition of myogenic tone by sodium nitroprusside, a direct smooth muscle relaxant, was unaltered in both rat and human T2D arteries. Treatment with a threshold concentration of SKA-31 (0.3 μM) significantly enhanced vasodilatory responses to ACh and BK in arteries from T2D Goto-Kakizaki rats and human subjects, whereas only modest effects were observed in non-diabetic arteries of both species. Mechanistically, SKA-31 enhancement of evoked dilation was independent of vascular NO synthase and COX activities. Remarkably, SKA-31 treatment improved agonist-stimulated Ca(2+) elevation in acutely isolated endothelial cells from T2D Goto-Kakizaki cremaster and cerebral arteries, but not from Wistar control vessels. In contrast, SKA-31 treatment did not affect intracellular Ca(2+) release by the sarco/endoplasmic reticulum Ca(2+)-ATPase (SERCA) inhibitor cyclopiazonic acid. CONCLUSIONS: Collectively, our data demonstrate that KCa channel modulation can acutely restore endothelium-dependent vasodilatory responses in T2D resistance arteries from rats and humans, which appears to involve improved endothelial Ca(2+) mobilization.